GRAMMARS OF SLAVIC LANGUAGES FOR FRENCHSPEAKING PUBLIC - Chovancova, Katarina (European Scientific Journal, ESJ, 2014)
The paper deals with grammars for foreigners from the point of view of linguistically heterogeneous communication situations. It puts the notion of grammar through to those of mediation and intercomprehension. It brings an overview of existing grammars of Slavic languages for French-speaking users in a chronological and enunciative perspectives, focusing especially on the grammars of Slovak language as starting points of the conception of a new grammar of Slovak language for French-speaking public.